Editorial: New Iranian Strategic Plan on Addiction Biology Studies Has a Clear Message for Neuroscientists; “Your Help is Seriously Needed” - Hamed Ekhtiari; Mohammad-Taghi Joghataei; Mohammad-Reza Zarrindast (Basic and Clinical Neuroscience, 2011)
The fifth Iranian national congress on the biology of addiction was held in 22-24 June 2011 in Tehran University of Medical Sciences with over 100 valuable oral and poster presentations and over 300 participants. One of the main sessions of the congress was devoted to a national strategic planning and Iranian Drug Control Head Quarter (DCHQ) introducing the first national executive road map on research into the biology of addiction. The road map will serve as a part of national strategic plan on addiction studies in Iran. As the main contributors in the preparation of the map, we think neuroscientists have to play a unique role in implementation of this map. We believe that the studies into the biology of addiction can act as a pivotal turning point to promote neuroscience in Iran regarding the governmental focus and public demand on addiction prevention and treatment. In this editorial, we will elucidate a general schema of the map, focusing more on potential opportunities for neuroscientists, and discuss new hopes, needs and challenges that we would be facing in the future to take advantage of addiction related opportunities to study neuroscience in both national and international levels.